Aplicação de técnicas de inteligência computacional no apoio à decisão em jogo de empresas - Barros Junior, Daniel Ferreira de (2014)
The business games present themselves as differentiated pedagogical tool for directing the focus of the class and the dynamics of student learning. The efforts in developing business games result in several solutions. However, a typical problem in these teaching tools is the access of the student to feedback or online assistance of the simulation, mainly due to the number of teams involved in the game and the amount of data generated by simulations. This challenge was observed in the game, called SIMULADOR DE ADMINISTRAÇÃO EMPRESARIAL (SAE), for teaching the concepts of production management, sales and business strategies. This study investigates the use of computational intelligence techniques, including Artificial Neural Networks, Fuzzy Logic, Decision Trees, Multiagent Systems and techniques of the Data Mining, to support the decision of the players and the teacher during the simulations in the game, mainly aiming at reducing the problems of feedback to the player and increasing dynamics of the game.